Coating agent, coating film, and laminate
By using a combination coating agent of acid-modified polyolefin resin, epoxy compound and aqueous medium, the problem of difficulty in improving the adhesion, heat resistance and dielectric properties of the substrate and copper foil in the prior art are solved, and efficient transmission loss suppression is achieved, and suitable for high-frequency printed wiring boards and general resin substrates.
Patent Information
- Application Number
- CN202380061666.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-30
- Filing Date
- 2023-08-25
- Publication Date
- 2025-04-04
AI Technical Summary
In the prior art, when using an aqueous adhesive to bond a liquid crystal resin or polyimide resin base material to a copper foil, it is difficult to simultaneously improve the adhesiveness, repeated welding heat resistance and dielectric characteristics, and there is a problem of large transmission loss.
A coating agent containing an acid-modified polyolefin resin, an epoxy compound and an aqueous medium is used to form a coating film with excellent adhesion and dielectric properties through a specific proportion, thereby suppressing the transmission loss of the laminated body.
Excellent adhesion with liquid crystal resin or polyimide resin substrate and copper foil is achieved, heat resistance of repeated welding is improved, and transmission loss is significantly suppressed. It is suitable for high-frequency printed wiring boards and general polyester resin substrates.
Smart Images

Figure BDA0005283371120000151
Abstract
Description
Technical Field
[0001] The present invention relates to a coating agent, a coating film and a laminate. Background Art
[0002] In recent years, the transmission speed of signals in printed wiring boards has been increasing, and materials with excellent dielectric properties (low dielectric constant, dielectric loss tangent) in the high-frequency region are required. In response to such requirements, polyimide resins or liquid crystal resins (LCP) with excellent dielectric properties have been proposed as resins constituting the base material of printed wiring boards.
[0003] Patent Document 1 discloses an aqueous adhesive that is excellent in adhesion to a liquid crystal resin substrate and a thermoplastic resin substrate (Patent Document 1).
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2009-235290 Summary of the invention
[0007] In a laminate obtained by bonding a substrate and a copper foil using the aqueous adhesive disclosed in Patent Document 1, it is required to further improve the adhesiveness and repeated soldering heat resistance, improve the dielectric properties of the adhesive layer, and suppress the transmission loss.
[0008] The present invention is based on the above-mentioned problems of the prior art and aims to provide a coating agent as a technical problem, which can form a coating film with excellent adhesion to a substrate composed of a liquid crystal resin or a polyimide resin and a metal foil and excellent dielectric properties, and can suppress the transmission loss of the obtained laminate to a low level.
[0009] The present inventors have conducted intensive studies to solve the above problems and have found that a coating agent containing a specific acid-modified polyolefin resin and a specific epoxy compound at a specific ratio and containing an aqueous medium can solve the above problems, thereby completing the present invention.
[0010] That is, the gist of the present invention is as follows.
[0011] The coating agent of the present invention comprises an acid-modified polyolefin resin (A), an epoxy compound (B), and an aqueous medium, and is characterized in that:
[0012] The acid-modified polyolefin resin (A) contains 0.1 to 10% by mass of an unsaturated carboxylic acid component.
[0013] The epoxy equivalent of the epoxy compound (B) is 500 or less, and the content thereof is 0.2 parts by mass or more and less than 5 parts by mass based on 100 parts by mass of the acid-modified polyolefin resin (A).
[0014] According to the coating agent of the present invention, the epoxy resin (B) preferably contains an epoxy compound having three or more epoxy groups in one molecule.
[0015] According to the coating agent of the present invention, the epoxy resin (B) is preferably at least one selected from the group consisting of sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether and glycerol polyglycidyl ether.
[0016] According to the coating agent of the present invention, the acid-modified polyolefin resin (A) preferably contains 3 to 25% by mass of a (meth)acrylate component.
[0017] According to the coating agent of the present invention, for a laminate obtained by laminating a substrate composed of a liquid crystal resin or a polyimide resin, a coating film obtained from the coating agent, and a copper foil and performing a heat sealing process, the bonding strength when the substrate and the copper foil are peeled off in a direction of 90° at a tensile speed of 50 mm / min is preferably 0.8 kN / m or more.
[0018] The coating film of the present invention is a coating film obtained from the above-mentioned coating agent.
[0019] According to the coating film of the present invention, it is preferred that the relative dielectric constant measured at a frequency of 10 GHz is 3.0 or less, and the dielectric loss tangent is 0.01 or less.
[0020] The laminate of the present invention is a laminate in which a substrate composed of a liquid crystal resin or a polyimide resin, the above-mentioned coating film, and a metal foil are laminated in this order.
[0021] A printed wiring board of the present invention is a printed wiring board including the above-mentioned laminate.
[0022] The coating obtained from the coating agent of the present invention has excellent adhesion to a substrate composed of a liquid crystal resin or a polyimide resin and a metal foil, and further has excellent heat resistance to repeated soldering treatments, and in addition, has excellent dielectric properties, so that the transmission loss can be suppressed to a low level in the laminate. Therefore, the coating agent of the present invention can be applied to the stacking of a printed wiring board corresponding to a high frequency that could not be applied in the past. Furthermore, it can also be applied to the bonding of a polyester resin substrate or the like that is generally sold with a metal foil, and is therefore a coating agent with excellent versatility of the substrate. DETAILED DESCRIPTION
[0023] Hereinafter, the present invention will be described in detail.
[0024] The coating agent of the present invention contains an acid-modified polyolefin resin (A), an epoxy compound (B), and an aqueous medium. In the coating agent of the present invention, the acid-modified polyolefin resin (A) is preferably dispersed in the aqueous medium.
[0025] <Acid-modified polyolefin resin (A)>
[0026] The acid-modified polyolefin resin (A) is a copolymer containing an unsaturated carboxylic acid component and an olefin component as copolymerization components. The coating agent of the present invention contains the acid-modified polyolefin resin (A) in which the polyolefin resin is acid-modified with an unsaturated carboxylic acid component, thereby improving the coating property and film-forming property on the substrate.
[0027] The unsaturated carboxylic acid component is composed of an unsaturated carboxylic acid and an anhydride thereof. Specifically, the unsaturated carboxylic acid component includes acrylic acid, methacrylic acid, maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, fumaric acid, crotonic acid, etc., as well as half esters and half amides of unsaturated dicarboxylic acids. Among them, acrylic acid, methacrylic acid, maleic acid, and maleic anhydride are preferred, and acrylic acid and maleic anhydride are particularly preferred.
[0028] The content of the unsaturated carboxylic acid component in the acid-modified polyolefin resin (A) is 0.1 to 10% by mass, preferably 0.2 to 8% by mass, and more preferably 0.5 to 6% by mass. If the content of the unsaturated carboxylic acid component in the acid-modified polyolefin resin (A) is less than 0.1% by mass, the acid-modified polyolefin resin (A) cannot be stably dispersed in an aqueous medium, and if it exceeds 10% by mass, the adhesion and dielectric properties of the formed coating film are poor, and the transmission loss of the obtained laminate becomes large.
[0029] Examples of the olefin component constituting the acid-modified polyolefin resin (A) include olefins having 2 to 6 carbon atoms such as ethylene, propylene, isobutylene, 1-butene, 1-pentene, and 1-hexene, and mixtures thereof may also be used. Among them, olefins having 2 to 4 carbon atoms such as ethylene, propylene, isobutylene, and 1-butene are preferred, and ethylene is more preferred.
[0030] From the viewpoint of dielectric properties of the obtained coating film, the content of the olefin component in the acid-modified polyolefin resin (A) is preferably 60% by mass or more, more preferably 80% by mass or more.
[0031] The acid-modified polyolefin resin (A) preferably contains a (meth)acrylate component for the purpose of improving the adhesion between the substrate composed of a liquid crystal resin or a polyimide resin and the metal foil. The content of the (meth)acrylate component in the acid-modified polyolefin resin (A) is preferably 3 to 25% by mass, more preferably 4 to 22% by mass, further preferably 5 to 20% by mass, and particularly preferably 6 to 18% by mass.
[0032] As the (meth)acrylate component, there can be mentioned the esterification product of (meth)acrylic acid and alcohol having 1 to 30 carbon atoms, among which, from the viewpoint of easy availability, the esterification product of (meth)acrylic acid and alcohol having 1 to 20 carbon atoms is preferred. As specific examples of such compounds, there can be mentioned methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, lauryl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, etc. A mixture thereof can also be used. Among these, from the viewpoint of improving the adhesion between the substrate composed of liquid crystal resin or polyimide resin and the metal foil, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, hexyl acrylate, octyl acrylate are more preferred, ethyl acrylate and butyl acrylate are more preferred, and ethyl acrylate is particularly preferred. It should be noted that "(meth)acrylic acid-" means "acrylic acid- or methacrylic acid-".
[0033] In addition, the acid-modified polyolefin resin (A) may contain other components in an amount of about 10% by mass or less of the acid-modified polyolefin resin (A) in addition to the above components. As other components, olefins and dienes having a carbon number of more than 6, such as 1-octene and norbornene, maleic acid esters such as dimethyl maleate, diethyl maleate, and dibutyl maleate, (meth)acrylic acid amides, alkyl vinyl ethers such as methyl vinyl ether and ethyl vinyl ether, vinyl esters such as vinyl formate, vinyl acetate, vinyl propionate, vinyl pivalate, and vinyl versatate, and vinyl alcohol obtained by saponifying vinyl esters with alkaline compounds, etc., 2-hydroxyethyl ester, glycidyl (meth)acrylate, (meth)acrylonitrile, styrene, substituted styrene, carbon monoxide, sulfur dioxide, etc., and mixtures thereof may also be used.
[0034] The acid-modified polyolefin resin (A) may contain an N-substituted amide structure in which the hydroxyl group of the carboxyl group is substituted with an N,N-dimethylamino group, an N,N-diethylamino group or the like.
[0035] The melting point of the polyolefin resin is preferably 50 to 150° C., more preferably 60 to 130° C., and more preferably 70 to 110° C. If the melting point is less than the above range, the cohesive force may be weakened and the adhesiveness may be deteriorated. In addition, if the melting point exceeds the above range, the fluidity may be reduced, so the adhesiveness between the substrate composed of the liquid crystal resin or the polyimide resin and the metal foil may be reduced.
[0036] Examples of the acid-modified polyolefin resin (A) include ethylene-(meth)acrylic acid copolymers, ethylene-(meth)acrylic acid-maleic anhydride copolymers, acid-modified polyethylene, acid-modified polypropylene, acid-modified ethylene-propylene resins, acid-modified ethylene-butene resins, acid-modified propylene-butene resins, acid-modified ethylene-propylene-butene resins, or ethylene-(meth)acrylic acid ester-unsaturated carboxylic acid copolymers obtained by further modifying these acid-modified resins with (meth)acrylic acid esters or the like. Among them, ethylene-(meth)acrylic acid-maleic anhydride copolymers are preferred. Furthermore, the acid-modified polyolefin resin may be chlorinated in the range of 5 to 40% by mass.
[0037] As the acid-modified polyolefin resin (A), commercially available products such as the BONDINE series manufactured by Arkema, the VESTOPLAST series manufactured by EVONIK JAPAN, the PRIMACOR series manufactured by Dow Chemical, the UMEX series manufactured by Sanyo Chemical, the ADMER series manufactured by Mitsui Chemicals, and the TOYO-TAC series manufactured by Toyobo Co., Ltd. can be used. In addition, commercially available water-based acid-modified polyolefin resins such as the SUPERCHLON series manufactured by Nippon Paper Chemicals, the ZAIKTHENE series manufactured by Sumitomo Seika, the CHEMIPEARL series manufactured by Mitsui Chemicals, and the HARDLEN series manufactured by Toyobo Co., Ltd. can be used.
[0038] <Epoxy compound (B)>
[0039] The coating agent of the present invention contains an epoxy compound (B) for the purpose of improving adhesiveness and heat resistance.
[0040] From the aspect of improving adhesion and heat resistance, the epoxy compound (B) preferably has two or more epoxy groups in the molecule, and more preferably contains three or more epoxy groups. As the epoxy compound (B), bisphenol A type epoxy resin, bisphenol F type epoxy resin, novolac type epoxy resin, alicyclic epoxy resin, dicyclopentadiene type epoxy resin, biphenyl type epoxy resin, naphthalene type epoxy resin, ethylene glycol diglycidyl ether, propylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, trimethylolpropane polyglycidyl ether, pentaerythritol tetraglycidyl ether, sorbitol polyglycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, etc. can be cited. From the perspective of obtaining high adhesion, it is preferably selected from sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, and glycerol polyglycidyl ether. One or more.
[0041] The epoxy equivalent (g / eq.) of the epoxy compound (B) is 500 or less, preferably 400 or less, more preferably 300 or less, further preferably 200 or less, and particularly preferably 150 or less. If the epoxy equivalent of the epoxy compound (B) exceeds 500, the adhesion and dielectric properties of the obtained coating film to the substrate composed of a liquid crystal resin or a polyimide resin and the metal foil are reduced, and the transmission loss of the obtained laminate becomes larger. The lower limit of the epoxy equivalent is not particularly limited, for example, 80.
[0042] The content of the epoxy compound (B) is 0.2 parts by mass or more and less than 5 parts by mass, preferably 0.5 to 4.5 parts by mass, and more preferably 1.0 to 4.0 parts by mass, relative to 100 parts by mass of the acid-modified polyolefin resin. For the coating agent, if the content of the epoxy compound (B) is less than 0.2 parts by mass, the adhesion, heat resistance, and durability of heat resistance between the substrate composed of the liquid crystal resin or the polyimide resin and the metal foil are poor, and if it is 5 parts by mass or more, the adhesion between the substrate and the metal foil is reduced, the dielectric properties of the obtained coating film are reduced, and the transmission loss of the obtained laminate is increased.
[0043] <Aqueous medium>
[0044] The aqueous medium constituting the coating agent of the present invention is water or a liquid containing water as a main component. From the environmental point of view, it is preferable to use an aqueous medium.
[0045] The aqueous medium may contain a basic compound or a hydrophilic organic solvent. The aqueous medium containing a hydrophilic organic solvent improves the wettability of the coating agent to the substrate, and achieves the effect of improving coating properties and film-forming properties.
[0046] In order to impart appropriate wettability to the substrate, the content of the hydrophilic organic solvent is preferably 1 to 50% by mass, more preferably 3 to 30% by mass, and even more preferably 5 to 25% by mass, based on the total amount of the coating agent.
[0047] Examples of the hydrophilic organic solvent include alcohols such as methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, sec-butanol, tert-butanol, n-pentanol, isopentanol, sec-pentanol, tert-pentanol, 1-ethyl-1-propanol, 2-methyl-1-butanol, n-hexanol, and cyclohexanol; ketones such as methyl ethyl ketone, methyl isobutyl ketone, ethyl butyl ketone, and cyclohexanone; tetrahydrofuran, dihydrofuran, and cyclohexanone; ethers such as alkyl; esters such as ethyl acetate, n-propyl acetate, isopropyl acetate, n-butyl acetate, isobutyl acetate, sec-butyl acetate, 3-methoxybutyl acetate, methyl propionate, ethyl propionate, diethyl carbonate, dimethyl carbonate; glycol derivatives such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, ethylene glycol monobutyl ether, ethylene glycol ethyl ether acetate; further, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, 3-methoxy-3-methyl-1-butanol, methoxybutanol, acetonitrile, dimethylformamide, dimethylacetamide, diacetone alcohol, ethyl acetoacetate, 1,2-dimethylglycerol, 1,3-dimethylglycerol, or trimethylglycerol.
[0048] Examples of the basic compound include ammonia, triethylamine, N,N-dimethylethanolamine, isopropylamine, aminoethanol, dimethylaminoethanol, diethylaminoethanol, ethylamine, diethylamine, isobutylamine, dipropylamine, 3-ethoxypropylamine, 3-diethylaminopropylamine, sec-butylamine, propylamine, n-butylamine, 2-methoxyethylamine, 3-methoxypropylamine, 2,2-dimethoxyethylamine, monoethanolamine, morpholine, N-methylmorpholine, N-ethylmorpholine, pyrrole, pyridine, and the like.
[0049] <Additives>
[0050] The coating agent of the present invention may contain additives such as a crosslinking agent and a curing accelerator other than the epoxy compound (B) in order to further improve performance according to the purpose.
[0051] The crosslinking agent is not particularly limited, and examples thereof include self-crosslinking crosslinking agents, compounds having multiple functional groups that react with carboxyl groups in the molecule, and metals having a multivalent coordination number. Specifically, isocyanate compounds, melamine compounds, urea compounds, carbodiimide compounds, Oxazoline compounds, zirconium salt compounds, silane coupling agents, etc. In addition, these crosslinking agents may be used in combination in plurality.
[0052] The content of the crosslinking agent is preferably 0.01 to 30 parts by mass, more preferably 0.1 to 20 parts by mass, and further preferably 0.5 to 10 parts by mass relative to 100 parts by mass of the acid-modified polyolefin resin (A). When the content of the crosslinking agent is less than 0.01 parts by mass, the formed coating film cannot be expected to have a tendency to improve performance, and when the content exceeds 30 parts by mass, the dielectric properties of the formed coating film may sometimes decrease.
[0053] The coating agent of the present invention may contain a curing accelerator. The curing accelerator is not particularly limited, and examples thereof include tertiary amine curing agents, tertiary amine salt curing agents, imidazole curing agents, and phosphate curing accelerators.
[0054] The content of the curing accelerator is preferably 1 to 100 parts by mass, more preferably 3 to 70 parts by mass, based on 100 parts by mass of the epoxy compound (B).
[0055] The coating agent of the present invention may further contain various additives such as a surfactant, a leveling agent, a defoaming agent, a wax inhibitor, a pigment dispersant, an ultraviolet absorber, a weathering agent, and a flame retardant as required.
[0056] The coating agent of the present invention preferably contains substantially no nonvolatile water-based additive. The present invention does not exclude the use of a nonvolatile water-based additive, but even without using a water-based additive, the acid-modified polyolefin resin (A) can be dispersed in an aqueous medium in a fine and stable manner.
[0057] The nonvolatile aqueous dispersing aid is an agent or compound added for the purpose of promoting aqueous dispersibility or stabilizing aqueous dispersions. "Nonvolatile" means having no boiling point at normal pressure or having a high boiling point (eg, 300° C. or higher) at normal pressure.
[0058] “Substantially free of non-volatile aqueous dispersing aids” means that such aids are not used during production (during aqueous dispersing of the acid-modified polyolefin resin (A)), and the resulting aqueous dispersion does not contain such aids in the end. The non-volatile aqueous dispersing aid is preferably 5% by mass or less, more preferably 2% by mass or less, further preferably less than 0.5% by mass, and particularly preferably 0% by mass, relative to the acid-modified polyolefin resin (A).
[0059] Examples of the nonvolatile aqueous dispersing aid include emulsifiers, compounds having a protective colloid action, modified waxes, acid-modified compounds having a high acid value, and water-soluble polymers.
[0060] <Coating agent>
[0061] The coating agent of the present invention contains an acid-modified polyolefin resin (A), an epoxy compound (B), and an aqueous medium, and the carboxyl group-containing acid-modified polyolefin resin (A) is preferably dispersed in the aqueous medium.
[0062] The content of the non-volatile component in the coating agent of the present invention can be appropriately selected according to the coating conditions, the thickness or performance of the intended coating film, etc., and is not particularly limited, but is preferably 1 to 60% by mass, more preferably 3 to 55% by mass, further preferably 5 to 50% by mass, and particularly preferably 10 to 45% by mass in terms of maintaining an appropriate viscosity and exhibiting good film-forming properties.
[0063] From the viewpoint of coating properties on a substrate, the viscosity of the coating agent of the present invention is preferably 1 to 2000 mPa·s, more preferably 3 to 1000 mPa·s, and even more preferably 5 to 500 mPa·s.
[0064] The method for producing the coating agent of the present invention is not particularly limited, and may be a method of mixing the above-mentioned raw materials, and the order of mixing them is arbitrary. The acid-modified polyolefin resin (A) may be mixed in the form of an aqueous dispersion dispersed in an aqueous medium.
[0065] <Coating>
[0066] To base materials such as film or nonwoven fabric, the coating agent of the present invention can be coated with known coating methods and made into the coating film of the present invention. For example, by gravure roller coating, reverse roller coating, wire rod coating, die lip coating, air knife coating, curtain flow coating, spraying, dip coating, brush coating, etc., uniformly coated on the substrate surface, by being provided for the heat treatment for drying, thus can be formed by close contact with the substrate surface. As a heating device, a common hot air circulation type oven or infrared heater, etc. can be used. In addition, the heating temperature and the heating time can be appropriately selected considering economy, etc.
[0067] The coating film of the present invention preferably has a thickness of 1 to 30 μm, more preferably 2 to 20 μm, and even more preferably 3 to 15 μm. When the thickness is within the above range, the formed coating film has high adhesiveness.
[0068] In order to adjust the thickness of the coating film, in addition to appropriately selecting the device for coating and its use conditions, it is preferred to use a coating agent with a concentration suitable for the intended thickness. The concentration of the coating agent can be adjusted according to the feed composition during preparation, and in addition, the coating agent temporarily prepared can be appropriately diluted or concentrated to adjust.
[0069] The coating film of the present invention is a coating film having excellent dielectric properties, and preferably has a relative dielectric constant of 3.0 or less and a dielectric loss tangent of 0.01 or less, as measured at a frequency of 10 GHz, more preferably a relative dielectric constant of 2.8 or less and a dielectric loss tangent of 0.008 or less, and further preferably a relative dielectric constant of 2.6 or less and a dielectric loss tangent of 0.006 or less.
[0070] <Laminated body>
[0071] The laminate of the present invention is a laminate comprising the coating film of the present invention, and examples thereof include laminates comprising the coating film of the present invention on various substrate surfaces, adhesive layers, or primer layers.
[0072] The coating agent of the present invention has excellent adhesion to a substrate composed of a liquid crystal resin or a polyimide resin and a metal foil, so the laminate preferably contains a coating film formed by the coating agent of the present invention and a metal foil in this order on a substrate composed of a liquid crystal resin or a polyimide resin.
[0073] (Base material)
[0074] The liquid crystal resin constituting the substrate refers to a polymer that shows a state in which the molecular chains are arranged in a nearly regular manner (liquid crystallinity) when the resin becomes a fluid state by melting at high temperature or dissolving in a solvent. For example, some resins such as wholly aromatic polyesters, aromatic polyazomethines, aromatic aliphatic polyesters, aromatic polyester carbonates, and wholly aromatic or non-wholly aromatic polyester amides are known to show liquid crystallinity.
[0075] Examples of polyesters known as liquid crystal resins include polyesters obtained by linear polycondensation of p-hydroxybenzoic acid and other components, specifically polyesters obtained by polycondensation of ethylene terephthalate and p-hydroxybenzoic acid, polyesters obtained by polycondensation of phenol and phthalic acid and p-hydroxybenzoic acid, and polyesters obtained by polycondensation of 2,6-hydroxynaphthoic acid and p-hydroxybenzoic acid.
[0076] Liquid crystal resins can be obtained from commercial products. For example, VECTRA series "A950, E951SX" manufactured by POLYPLASTICS, SUMIKASUPER series "E5204L, E6807LHF" manufactured by Sumitomo Chemical, RODRUN series "LC5030G, LC5030MF" manufactured by UNITIKA, etc. These can be mixed with fillers to improve their elasticity and strength, or ester amidation can be used to improve their elastic modulus.
[0077] The substrate composed of a liquid crystal resin can also be obtained from commercially available products, for example, VECSTAR series manufactured by Kuraray Co., Ltd., etc. are mentioned.
[0078] As the substrate composed of polyimide resin, a film form can be cited. For example, the following method can be cited: a polyamic acid (polyimide precursor) solution is obtained by reacting diamines and tetracarboxylic acids, the solution is applied to a substrate for making a polyimide film and dried to make a precursor film, and then the polyimide film is obtained by peeling it from the substrate or directly performing a high-temperature heat treatment to perform a dehydration ring-closure reaction.
[0079] Examples of the diamine component constituting the polyimide resin include p-phenylenediamine (PDA), 4,4′-diaminodiphenyl ether (ODA), 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP), m-phenylenediamine, 2,4-diaminotoluene, 4,4′-diaminobiphenyl, 4,4′-diamino-2,2′-bis(trifluoromethyl)biphenyl (PFMB), 2,2′-dimethyl-4,4′-diaminobiphenyl (DMDB), 3,3′-diaminodiphenyl sulfone, 4,4′-diaminodiphenyl sulfide, 4,4′-diaminodiphenylmethane, 3,4′-diaminodiphenyl sulfone, 4,4′-diaminodiphenyl sulfide, 4,4′-diaminodiphenylmethane, 3,4′-diaminodiphenyl sulfone, 4,4′-diaminodiphenyl sulfide, 4,4′-diaminodiphenyl m ... Diaminodiphenyl ether, 3,3′-diaminodiphenyl ether, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 4,4′-bis(4-aminophenoxy)biphenyl, bis[4-(4-aminophenoxy)phenyl]sulfone, bis[4-(3-aminophenoxy)phenyl]sulfone, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 1,3-bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, bis(aminomethyl)norbornane, 3(4),8(9)-bis(aminomethyl)tricyclo[5.2.1.0 2,6 ] decane, 1,3-cyclohexanediamine, 1,4-cyclohexanediamine, isophoronediamine, 4,4′-methylenebis(cyclohexylamine), 4,4′-methylenebis(2-methylcyclohexylamine), 1,4-diaminobutane, 1,10-diaminodecane, 1,12-diaminododecane, 1,7-diaminoheptane, 1,6-hexanediamine, 1,5-pentanediamine, 1,8-diaminooctane, 1,3-diaminopropane, 1,11-diaminoundecane, 2-methyl-1,5-diaminopentane, dimer diamine and the like.
[0080] These may be used alone or in combination of two or more.
[0081] Examples of the tetracarboxylic acid component constituting the polyimide resin include pyromellitic dianhydride (PMDA), 3,3′,4,4′-biphenyltetracarboxylic dianhydride (BPDA), 2,3,3′,4′-biphenyltetracarboxylic dianhydride, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA), 4,4′-oxydiphthalic dianhydride (ODPA), 3,3′,4,4′-diphenylsulfonetetracarboxylic dianhydride, 4,4′-(hexafluoroisopropylene)diphthalic dianhydride (6FDA), and 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride (BPADA). These may be used alone or in combination of two or more.
[0082] As the polyimide resin substrate, a commercially available polyimide film can be used, for example, "KAPTON" (a trade name manufactured by Toray DuPont Co., Ltd.), "UPILEX" (a trade name manufactured by Ube Industries, Ltd.), etc. In addition, a substrate coated with a modified polyimide (MPI) film or a modified polyimide (MPI) varnish can also be used.
[0083] These polyimide films can be subjected to chemical or physical surface treatment. As chemical surface treatment, surface treatment using silane coupling agent, aluminum alcoholate, etc. can be cited. On the other hand, as physical surface treatment, surface roughening treatment, plasma treatment, etc. can be cited. However, the coating agent of the present invention is also excellent in adhesion to substrates that are not subjected to surface treatment.
[0084] In addition, the coating agent of the present invention also has excellent adhesion to other general-purpose resin substrates and metal foils. Examples of general-purpose resin substrates include polyester resin substrates, polycarbonate resin substrates, polyphenylene sulfide resin substrates, cycloolefin resin substrates, polyethylene resin substrates, polypropylene resin substrates, and semi-aromatic polyamide resin substrates.
[0085] (metal foil)
[0086] The metal foil is not particularly limited, and examples thereof include metal foils made of copper, nickel, aluminum, and the like.
[0087] The laminate of the present invention can be used for, for example, a bonding sheet, a copper foil with a resin, a cover film, a printed wiring board, a copper-clad laminate, a flat cable, a wiring board for tape automated bonding, an electromagnetic wave shielding material, and the like.
[0088] Example
[0089] Hereinafter, the present invention will be specifically described based on examples, but the present invention is not limited to these examples.
[0090] Various properties were measured or evaluated by the following methods.
[0091] 1. Bonding strength
[0092] The coating agent was applied to a liquid crystal resin substrate, a polyimide resin substrate, or a polyester resin substrate using a bar coater in a manner such that the coating thickness after drying was 10 μm, and then dried at 100°C × 1 minute using a hot air dryer. Then, the copper foil was bonded to the coated surface and heat-sealed for 60 seconds at a temperature of 200°C and a pressure of 0.2 MPa. Then, the bonded laminate was cut into a width of 10 mm, and the substrate and copper foil were peeled off at a tensile speed of 50 mm / min in a 90-degree direction at an atmosphere of 23°C. The adhesion was evaluated according to the following criteria.
[0093] ◎: 1.20kN / m or more
[0094] ○: 1.00 kN / m or more and less than 1.20 kN / m
[0095] △: 0.80kN / m or more and less than 1.00kN / m
[0096] ×: less than 0.80 kN / m
[0097] 2. Relative dielectric constant, dielectric loss tangent
[0098] The coating agent was applied to a release film (NAFLON PTFE tape manufactured by TOMBO, thickness 200 μm) in such a manner that the coating thickness after drying was 30 μm, and dried at 100°C / 10 minutes to form a coating film. Then, the coating film was peeled off from the release film to prepare a sheet for measurement. The obtained sheet was measured at 23°C atmosphere under the condition of a frequency of 10 GHz using a separation dielectric resonator method.
[0099] The relative dielectric constant was evaluated according to the following criteria.
[0100] ◎: 2.60 or less
[0101] ○: more than 2.60 and less than 2.80
[0102] △: More than 2.80 and less than 3.00
[0103] ×: more than 3.00
[0104] The dielectric loss tangent was evaluated according to the following criteria.
[0105] ◎: 0.0060 or less
[0106] ○: more than 0.0060 and less than 0.0080
[0107] △: more than 0.0080 and less than 0.0100
[0108] ×: more than 0.0100
[0109] 3. Transmission loss (S21)
[0110] Use a bar coater to apply the coating agent to both sides of the liquid crystal resin substrate in a manner that the coating thickness after drying is 10μm, and then use a hot air dryer to dry at 100℃×1 minute. Then, bond the coated surfaces of both sides to the copper foil and perform heat sealing for 30 minutes under vacuum, temperature 200℃, and pressure 3.0MPa. Then, form a microstrip line with a characteristic impedance of 50Ω by bonding the laminated body, and measure the transmission loss between 10MHz and 40GHz (using KEYSIGHT TECHNOLOGY, network analyzer E5227B). Evaluate the transmission loss according to the following criteria.
[0111] ○: The absolute value of the transmission loss at 30 GHz is less than 5.0 dB / 100 mm
[0112] ×: The absolute value of the transmission loss at 30 GHz is 5.0 dB / 100 mm or more
[0113] 4. Solder heat resistance (heat resistance)
[0114] A laminate was prepared using a liquid crystal resin substrate as a substrate according to the method described in the above "1. Bonding Strength". A 2.5 cm × 2.5 cm sample piece was dried at 120°C for 30 minutes and flowed in a molten solder bath at 260°C for 1 minute. The solder heat resistance was evaluated by visual observation according to the following criteria.
[0115] ○: No expansion
[0116] △: Slightly expanded
[0117] ×: There is a large expansion
[0118] 5. Repeated soldering heat resistance (durability of heat resistance)
[0119] Samples were prepared by the method described in "4. Solder Heat Resistance (Heat Resistance)" above, and an operation of flowing in a molten solder bath at 260°C for 1 minute was repeated 10 times. Repeated solder heat resistance was evaluated by visual observation according to the following criteria.
[0120] ○: No expansion
[0121] △: Slightly expanded
[0122] ×: There is a large expansion
[0123] 6. Comprehensive evaluation
[0124] ○: The evaluation is “△” or above in any of the above “1. Adhesion strength”, “2. Relative dielectric constant, dielectric loss tangent”, “3. Transmission loss”, “4. Solder heat resistance (heat resistance)”, and “5. Repeated solder heat resistance (durability of heat resistance)”.
[0125] ×: An evaluation of “×” was given in any of the above “1. Adhesive strength”, “2. Relative dielectric constant, dielectric loss tangent”, “3. Transmission loss”, “4. Solder heat resistance (heat resistance)”, and “5. Repeated solder heat resistance (durability of heat resistance)”.
[0126] As the raw materials and base material of the coating agent, the following were used.
[0127] I. Aqueous dispersion (E) of acid-modified polyolefin resin (A)
[0128] E-1: Production of aqueous dispersion (E-1) of acid-modified polyolefin resin (A-1)
[0129] Using a stirrer equipped with a heater and a sealable 1L pressure-resistant glass container, 100 g of an acid-modified polyolefin resin (A-1) [ethylene-ethyl acrylate-maleic anhydride copolymer, 92% by mass of ethylene, 6% by mass of ethyl acrylate, 2% by mass of maleic anhydride, melting point 105° C.], 80 g of isopropyl alcohol, 4.0 g of N,N-dimethylethanolamine, and 220 g of water were placed in a glass container and heated and stirred at 130° C. for 60 minutes. Then, after cooling to room temperature while stirring, 150 g of water was added, and water and isopropyl alcohol were distilled off under reduced pressure using an evaporator, thereby obtaining an aqueous dispersion (E-1) of acid-modified polyolefin resin (A-1) particles.
[0130] E-2: Production of aqueous dispersion (E-2) of acid-modified polyolefin resin (A-2)
[0131] Aqueous dispersion (E-2) was obtained by the same operation as in the case of aqueous dispersion (E-1) except that an acid-modified polyolefin resin (A-2) [ethylene-ethyl acrylate-maleic anhydride copolymer, 80% by mass of ethylene, 18% by mass of ethyl acrylate, 2% by mass of maleic anhydride, melting point 83° C.] was used.
[0132] E-3: Production of aqueous dispersion (E-3) of acid-modified polyolefin resin (A-3)
[0133] 280 g of a propylene-ethylene copolymer (propylene / ethylene=81.8 / 18.2 (mass ratio), weight average molecular weight 85,000) was placed in a four-necked volumetric flask and heated to melt under a nitrogen atmosphere.
[0134] Then, the system temperature was maintained at 180°C, and 35.0 g of maleic anhydride as an unsaturated carboxylic acid and 6.0 g of di-tert-butyl peroxide as a free radical generator were added under stirring for 2 hours, and then reacted for 1 hour. After the reaction was completed, the obtained reactant was put into a large amount of acetone to precipitate the resin. The resin was then washed with acetone several times to remove the unreacted maleic anhydride, and then dried under reduced pressure in a reduced pressure dryer to obtain an acid-modified polyolefin resin (A-3) [mass ratio: propylene 75.4 / ethylene 16.8 / maleic anhydride 7.8, melting point 70°C].
[0135] Using the obtained resin, the same method as described in Japanese Patent Application No. 2005-506371 was carried out to obtain an aqueous dispersion (E-3) of a milky white acid-modified polyolefin resin (A-3).
[0136] E-4: Production of aqueous dispersion (E-4) of acid-modified polyolefin resin (A-4)
[0137] Acid-modified polyolefin resin (A-4) [ethylene-acrylic acid copolymer, ethylene 80 mass %, acrylic acid 20 mass %, melting point 79° C.] was used. Aqueous dispersion (E-4) was obtained by the same operation as in the case of aqueous dispersion (E-1) except for this.
[0138] II. Epoxy compounds (B)
[0139] B-1: Sorbitol polyglycidyl ether (Nagase ChemteX, Denacol EX-614, tetrafunctional epoxy compound (having four epoxy groups), epoxy equivalent 167)
[0140] B-2: Polyethylene glycol diglycidyl ether (Nagase ChemteX, Denacol EX-832, a bifunctional epoxy compound (having two epoxy groups), epoxy equivalent 284)
[0141] B-3: diglycerol polyglycidyl ether (Nagase ChemteX, Denacol EX-421, trifunctional epoxy compound, epoxy equivalent 159)
[0142] B-4: Glycerol polyglycidyl ether (Nagase ChemteX, Denacol EX-313, a complex of a bifunctional epoxy compound and a trifunctional epoxy compound, epoxy equivalent 141)
[0143] B-5: Polyethylene glycol diglycidyl ether (Nagase ChemteX, Denacol EX-861, difunctional epoxy compound, epoxy equivalent 551)
[0144] III. Copper foil
[0145] Adhesive strength measurement: Made by Hitachi Metals Neomaterial Co., Ltd., thickness 30 μm
[0146] Transmission loss measurement: Electrolytic copper foil manufactured by Fukuda Metal Foil Powder Co., Ltd., thickness 12 μm
[0147] IV. Substrate
[0148] Aromatic polyester liquid crystal resin obtained from hydroxynaphthoic acid and p-hydroxybenzoic acid Substrate: VECSTAR CTQ-50, manufactured by Kuraray Co., Ltd., thickness 50 μm
[0149] Polyimide resin substrate: UPILEX-S manufactured by Ube Industries, Ltd., thickness 50 μm
[0150] Polyester resin substrate: EMBLET S-50 manufactured by UNITIKA, thickness 50 μm
[0151] Example 1
[0152] An aqueous dispersion (E-1) of an acid-modified polyolefin resin (A-1) and an epoxy compound (B-1) were mixed at a solid content mass ratio of 100 / 1, and 20 parts by mass of isopropyl alcohol was added to 100 parts by mass of the mixed solution to prepare a coating agent.
[0153] Examples 2 to 9, Comparative Examples 1 to 4
[0154] As shown in Table 1, the coating agents were prepared by changing the types of the acid-modified polyolefin resin (A) and the epoxy compound (B) or the solid content mass ratio (content).
[0155] Table 1 shows the composition of the coating agents prepared in Examples and Comparative Examples and the evaluation results of various properties.
[0156]
[0157] The coating agents of Examples 1 to 9 have excellent adhesion to liquid crystal resin substrates or polyimide resin substrates and copper foil. The obtained coating films have excellent dielectric properties with low relative dielectric constant and dielectric loss tangent values, and the obtained laminates can suppress transmission loss at a low level and have excellent heat resistance (solder heat resistance). The coating agents also have excellent adhesion to polyester resin substrates and copper foil.
[0158] The coating agent of Comparative Example 1 has an epoxy compound content less than the range specified in the present invention, so has poor adhesiveness and poor heat resistance.
[0159] The content of the epoxy compound in the coating agent of Comparative Example 2 exceeded the range specified in the present invention, the dielectric properties of the coating film were poor, and the transmission loss of the laminate was large.
[0160] The coating agent of Comparative Example 3 had poor adhesiveness because it used an epoxy compound having an epoxy equivalent of more than 500. In addition, the transmission loss of the obtained laminate was large.
[0161] Since the coating agent of Comparative Example 4 has an unsaturated carboxylic acid component content of the acid-modified polyolefin resin exceeding the range specified in the present invention, high adhesion cannot be obtained, the dielectric properties of the coating film are poor, and the transmission loss of the laminate is large.
Claims
1. A coating agent comprising an acid-modified polyolefin resin (A), an epoxy compound (B), and an aqueous medium, characterized in that: The acid-modified polyolefin resin (A) contains 0.1 to 10% by mass of an unsaturated carboxylic acid component. The epoxy equivalent of the epoxy compound (B) is 500 or less, and the content thereof is 0.2 parts by mass or more and less than 5 parts by mass based on 100 parts by mass of the acid-modified polyolefin resin (A).
2. The coating agent according to claim 1, characterized in that The epoxy compound (B) includes an epoxy compound having three or more epoxy groups in one molecule.
3. The coating agent according to claim 1, characterized in that The epoxy compound (B) is at least one selected from the group consisting of sorbitol polyglycidyl ether, polyglycerol polyglycidyl ether, and glycerol polyglycidyl ether.
4. The coating agent according to any one of claims 1 to 3, characterized in that The acid-modified polyolefin resin (A) contains 3 to 25% by mass of a (meth)acrylate component.
5. The coating agent according to any one of claims 1 to 4, characterized in that For a laminate obtained by laminating a substrate composed of a liquid crystal resin or a polyimide resin, a coating obtained by a coating agent, and a copper foil and performing a heat sealing process, the bonding strength when the substrate and the copper foil are peeled off in a direction of 90° at a tensile speed of 50 mm / min is greater than 0.8 kN / m.
6. A coating film, characterized in that: This is obtained from the coating agent according to any one of claims 1 to 4.
7. The coating film according to claim 6, characterized in that The relative dielectric constant measured at a frequency of 10 GHz is 3.0 or less, and the dielectric loss tangent is 0.01 or less.
8. A laminated body comprising a substrate composed of a liquid crystal resin or a polyimide resin, the coating film according to claim 6, and a metal foil laminated in this order. 9 . A printed wiring board comprising the laminate according to claim 8 .
Citation Information
Patent Citations
Pharmaceutical composition for use in treating malignant tumors comprising in combination a bisphosphonate, a cox-2 inhibitor and taxol
JP2005506371A
Aqueous adhesive and laminated body using this adhesive
JP2009235290A